"Diagnostic Role of Bone Marrow Examination in Pediatric Hematologic Disorders" - Ashutosh Kumar Verma; Neha Shrivastava, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Bone marrow examination (BME) remains one of the most critical diagnostic tools in pediatric hematology, providing valuable insights into a wide range of hematological disorders. This paper reviews the role of bone marrow aspiration and biopsy in diagnosing and prognosticating pediatric hematologic conditions, including leukemia, anemia, idiopathic thrombocytopenic purpura (ITP), and various infections. The review synthesizes findings from multiple studies, with a focus on the diagnostic utility of BMB in pediatric populations, its complementarity with bone marrow aspiration (BMA), and its role in assessing disease progression and treatment response. The paper also explores the challenges of bone marrow examination in resource-limited settings and the necessity of prospective studies to refine clinical guidelines.